Evaluating English Teacher Performance at SMPN 31 Bengkulu Utara from the Student's Point of View - Ikhsan, Muhammad; Fadhli, Muhammad; Puspita, Hilda (UNIB Press, 2025)
This research was aimed to find out the student feedback on teacher Visual, Auditory, and Kinesthetic learning styles model in the English class. This research was conducted by using questionnaire patterns to reveal students’ point of view on their teacher’s performance consisted of a total of 25 closed-ended statements and utilized a Five-Point Likert Scale. The data was obtained from the questionnaire given by 135 students of 8th-grade from five different classes. Based on the data obtained, the results indicated that auditory strategies received the highest positive response at 90%, followed by kinesthetic activities at 93%, and visual strategies at 87%. The result obtained was shown that, kinesthetic strategies were found to increase student engagement significantly, with students validating the positive influence of proactive teacher attitudes in facilitating comprehension during English lessons. Auditory feedback emphasized students' ability to effectively absorb information through multi-sensory input, especially when auditory elements were integrated with kinesthetic learning. Visual strategies received moderately positive feedback because teachers only used traditional tools for visual-based teaching. It can be concluded that English teachers should improve and diversify their learning methods by integrating more interactive visuals, strengthening multi-sensory auditory practices, and continuing to apply engaging kinesthetic techniques to enhance student learning outcomes.